Risk factors for sensitisation and respiratory symptoms among workers exposed to acid anhydrides: a cohort study. - Barker, R; van Tongeren, M; Harris, J; Gardiner, K; Venables, K; Newman Taylor, A (1998)
OBJECTIVES: To examine the relation between exposure to acid anhydrides and the risk of developing immediate skin prick test responses to acid anhydride human serum albumin (AA-HSA) conjugates or work related respiratory symptoms; to assess whether these relations are modified by atopy or smoking. METHODS: A cohort of 506 workers exposed to phthalic (PA), maleic (MA), and trimellitic anhydride (TMA) was defined. Workers completed questionnaires relating to employment history, respiratory symptoms, and smoking habits. Skin prick tests were done with AA-HSA conjugates and common inhalant allergens. Exposure to acid anhydrides was measured at the time of the survey and a retrospective exposure assessment was done. RESULTS: Information was obtained from 401 (79%) workers. Thirty four (8.8%) had new work related respiratory symptoms that occurred for the first time while working with acid anhydrides and 12 (3.2%) were sensitised, with an immediate skin prick test reaction to AA-HSA conjugates. Sensitisation to acid anhydrides was associated with work related respiratory symptoms and with smoking at the time of exposure to acid anhydride. When all subjects were included and all three acid anhydrides were taken into account there was no consistent evidence for an exposure-response relation, but with the analysis restricted to a factory where only TMA was in use there was an increased prevalence of sensitisation to acid anhydrides and work related respiratory symptoms with increasing full shift exposure. This relation was apparent within the current occupational exposure standard of 40 micrograms.m-3 and was not modified significantly by smoking or atopy. CONCLUSIONS: Intensity of exposure and cigarette smoking may be risk factors for sensitisation to acid anhydrides. Exposure is also a risk factor for respiratory symptoms. As there was evidence for sensitisation to TMA at full shift exposures within the occupational exposure standard this standard should be reviewed.